Visual Communication and Its Relevance to Art Education on Murals at Tugu Tunas, Semarang City (Universitas Negeri Semarang, 2022)
The existence of a mural at Tugu Tunas has an important role as a medium of communication in public spaces. This mural is unique because it is applied to the monument field. This is different from most murals in general, bearing in mind that most murals occupy the walls of buildings with large fields of images. The purpose of this research is to analyze visual communication and its relevance to art education in the mural at Tugu Tunas, Semarang. This study uses a qualitative method with a phenomenological approach. Sources of data obtained from the process of field observations and interviews with a number of informants. Validating the data in this study used three stages of validating phenomenological data. The main idea in making or having a monument is